Recent Advances in Optically Active Polymer‐Based Nanowires and Nanotubes. Issue 12 (22nd September 2014) - Garreau, Alexandre; Duvail, Jean‐Luc
<x xml:space="preserve">Abstract</x> There is tremendous interest in one‐dimensional nanostructures, since they permit enhanced properties as well as new paradigms for electronic, optical, optoelectronic, and photonic devices. Besides inorganic systems, nanowires (NWs) and nanotubes (NTs) containing an optically active polymer are now being intensively investigated. This article reviews recent developments in the various preparation methods and in the optically related properties of polymer‐based NWs and NTs. The case of both conjugated polymers (CPs) and polymers containing photo‐active species is described herein. The latest developments in synthesis methods allow the design of NWs and NTs with improved features or with more complex architectures, including coaxial, (multi‐)segmented, hybrid, and composite systems. Consequently, it is possible to control and to tune their properties, as well as to reach new behaviors and multifunctionality. After a review of the fabrication methods, this paper focuses on the optical and optoelectronic features of polymer‐based NWs and NTs: electrochromism, photoluminescence and color control, electroluminescence, waveguiding and nanolasing effects, photoconductivity and photovoltaic devices, and plasmon‐coupled systems. The emphasis is on the emerging strategies for understanding and controlling the behavior of charges, excitons and photons, as required for developing the next generation of devices.